Studi kelayakan manajemen pembudidayaan ikan patin di Sambijajar, Sumbergempol, Tulungagung - Santoso, Eko; Rochman, Abdul; Prasetyo, Budi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The catfish cultivation commodity is a superior commodity. There are two models of catfish hatchery, namely integrated and unintegrated aquaculture. This study is to analyze the cost factor of catfish farming as well as efficiency and at the same time the income of the catfish farming management business. The research data collected were 32 respondents who cultivate catfish and were selected by purposive method and then analyzed using descriptive statistical methods. This study shows that the profit level of the integrated catfish hatchery business is greater than that of the unintegrated hatchery. This study also showed that the R-C Ratio of integrated catfish hatchery was higher than that of unintegrated catfish hatchery. From this research, it can be concluded that the integrated catfish hatchery is more profitable and more efficient than the unintegrated catfish hatchery